Analysis of the dynamic changes of endogenous hormones for the pericarp and seed kernel of young fruit in Camellia chekiangoleosa Hu. Issue 1 (31st December 2022) - Yu, Chunlian; Yao, Xiaohua; Wang, Kailiang; Huang, Guangyuan; Dong, Shuang; Long, Wei
Abstract : Camellia chekiangoleosa Hu. is a unique woody oil tree with significant economic and ornamental value in China, but the fruit is easily sunburned in low-altitude areas. However, few studies on their sunburn mechanism, especially the types and content of endogenous hormones with stress resistance, have not been reported, making it challenging to take reasonable preventive measures. Here, we analyzed the endogenous hormones before sunburn and found that salicylic acid (SA) and gibberellins (GAs) were very significantly correlated between pericarp and seed kernel. However, there weren't closely related to abscisic acid (ABA), auxin, jasmonic acids (JAs), and cytokinin. The content of indole-3-carboxylic acid (ICA) and 3-indolebutyric acid (IBA) in the pericarp was higher than in seed kernel, and IBA was only found in the pericarp. GAs in seed kernel were higher than that in pericarp, and GA3 and GA15 may regulate pericarp development. Contents of trans-Zeatin (tZ), indole-3-acetic acid (IAA), and GAs in seed kernel and pericarp gradually decreased to very low, while ABA and indole-3-carboxaldehyde (ICAld) gradually increased. SA was positively correlated with ABA in pericarp and GAs and SA in seed kernel and pericarp. JAs in fruit generally showed a downward trend, and methyl jasmonate (ME-JA) appeared in pericarp.